PENGARUH KOMPOSISI TERHADAP KARAKTERISTIK BRIKET KOMBINASI ARANG TEMPURUNG KELAPA DAN ARANG BAMBU - Ihsan, Ihsan; T, Muh. Asrianto (Universitas Islam Negeri Alauddin Makassar, 2019)
This research aims to determine the influence of variations of coconut shell charcoal and bamboo charcoal on briquette characteristics, thus obtained optimum composition that produces briquette with the best characteristic. This research is a laboratory experimentation study, with free variables being charcoal compositions, and bound variables are characteristic briquettes consisting of: Heat value, moisture content, and ignition length. The results showed that variations in the composition of briquette from coconut charcoal and bamboo charcoal influenced briquette characteristics, moisture value, moisture content, and the length of time of ignition. The highest heat value is obtained on the composition of 10% of bamboo charcoal and 90% of coconut shell Charcoal is 7110.73 cal/G with a water content of 4.82% and the length of time of 150.45 minutes.